Microporous-mesoporous x molecular sieve, method for preparing same, and use thereof

CN122957853APending Publication Date: 2026-10-23CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510509835.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,有机模板剂在合成后部分会保留在分子筛孔道内部,需要500℃以上高温进行焙烧,并且排放COx和NOx等温室气体,造成能耗的损失和环境的污染

Benefits of technology

[0020]通过上述技术方案,本公开的方法通过控制特定的晶化步骤和条件,限制EMT结构的产生,制备出的分子筛包括纳米粒子堆叠形成的晶粒的结构,且在XRD谱图中不存在EMT特征峰,具有较好的传质性能。该分子筛具有FAU晶相和适宜的孔道分布,含有微孔-介孔的多级孔道,有利于改善分子筛的传质能力和吸附容量,将其作为吸附剂用于C8芳烃同分异构体的吸附分离时,能够将对二甲苯分离出来,具有较高的吸附选择性和传质效率。本公开的制备方法不使用模板剂,避免了有机模板剂的焙烧过程,降低了分子筛的生产能耗以及COx和NOx等温室气体的排放,更加绿色环保。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122957853A_ABST
    Figure CN122957853A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a micropore-mesopore X molecular sieve, a preparation method and application thereof, the micropore-mesopore X molecular sieve comprises crystal grains stacked by nanoparticles; the micropore-mesopore X molecular sieve comprises a FAU crystal phase, and no characteristic peak of EMT exists in the XRD spectrum; in the micropore-mesopore X molecular sieve, the total amount of framework aluminum accounts for 90.0-99.0% of the total amount of aluminum, and the silicon in a chemical environment of Si(4Al, 0Si) accounts for 35.0-50.0% of the total amount of silicon; the total pore volume of the X molecular sieve is 0.30-0.45 cm 3 / g, the proportion of mesopore pore volume in the total pore volume is 3.0-50.0%, the proportion of micropore pore volume in the total pore volume is 50.0-97.0%, the most probable mesopore pore diameter is 2-15 nm, the micropore specific surface area is 720-760 m 2 / g, the mesopore specific surface area is 20-100 m 2 / g; the average particle size of the crystal grains is 0.8-5.0 μm. When the micropore-mesopore X molecular sieve is used as an adsorbent for the adsorption separation of C8 aromatic hydrocarbon isomers, it can separate p-xylene, and has high adsorption selectivity and mass transfer efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to X molecular sieves, specifically a microporous-mesoporous X molecular sieve, its preparation method, and its applications. Background Technology

[0002] X-type molecular sieves possess large micropores and a unique supercage structure, resulting in high adsorption capacity. Their low silica-to-alumina ratio provides abundant cation exchange sites, enabling the formation of strong electrostatic fields at specific structural locations, thus facilitating the adsorption of specific organic molecules. US3558730 and US3960774 both report that barium- or barium / potassium-ion-exchanged X-type molecular sieves can effectively and selectively adsorb p-xylene from C8 aromatics. Therefore, X-type molecular sieves are widely used as the active component of adsorbents for separating p-xylene from C8 mixed aromatics. Three important indicators for evaluating their adsorption performance are adsorption selectivity, adsorption capacity, and mass transfer capacity.

[0003] The adsorption selectivity of X-type molecular sieves for C8 aromatic isomers is mainly affected by the properties of the molecular sieve and the type of exchangeable cations. Conventional X-type molecular sieves with FAU topology have low mass transfer efficiency during adsorption. Studies have shown that the presence of mesoporous-microporous hierarchical channels is beneficial to improving intracrystalline mass transfer efficiency during adsorption. Currently, most reports on the synthesis of mesoporous X-type molecular sieves use organic template agents. CN107107026B and CN109692657B report the preparation of mesoporous X-type molecular sieves using a long-chain amphoteric organosilane (TPOAC) and an organic quaternary ammonium salt as organic template agents, respectively. However, some of the organic template agent remains inside the molecular sieve channels after synthesis, requiring calcination at temperatures above 500°C and emitting greenhouse gases such as COx and NOx, resulting in energy loss and environmental pollution. Summary of the Invention

[0004] The purpose of this disclosure is to provide a microporous-mesoporous X molecular sieve, its preparation method, and its application.

[0005] To achieve the above objectives, the first aspect of this disclosure provides a microporous-mesoporous X molecular sieve, wherein the microporous-mesoporous X molecular sieve comprises crystals formed by stacking nanoparticles; The microporous-mesoporous X molecular sieve includes the FAU crystalline phase, and the characteristic peaks of EMT are not present in the XRD pattern. In the microporous-mesoporous X molecular sieve, skeletal aluminum accounts for 90.0% to 99.0% of the total aluminum, and silicon with a chemical environment of Si(4Al, 0Si) accounts for 35.0% to 50.0% of the total silicon. The total pore volume of the X molecular sieve is 0.30~0.45 cm³. 3 / g, the proportion of mesopore volume to total pore volume is 3.0~50.0%, the proportion of micropore volume to total pore volume is 50.0~97.0%, the most probable pore size of mesopores is 2~15nm, and the specific surface area of ​​micropores is 720~760m². 2 / g, mesoporous specific surface area is 20~100m² 2 / g; The average grain size is 0.8~5.0 μm.

[0006] Optionally, the nanoparticles include nanosheets, wherein the size L of the nanosheets in the direction of the minimum size passing through the center is 50~500 nm; Optionally, in the microporous-mesoporous X molecular sieve, the molar ratio of silicon (calculated as SiO2) to aluminum (calculated as Al2O3) is 1.0 to 3.0.

[0007] Optionally, the cations in the microporous-mesoporous X molecular sieve include Na. + and / or K + ; In the microporous-mesoporous X molecular sieve, the total content of Na2O and K2O is 18.0~20.0% by weight.

[0008] A second aspect of this disclosure provides a method for preparing microporous-mesoporous X molecular sieves, the method comprising: (1) Mix an inorganic alkali containing metal elements, a silicon source, an aluminum source, and water to obtain a mixture; (2) The mixture is subjected to aging treatment to obtain an aging product; (3) The aging products are subjected to a first-stage crystallization treatment and a second-stage crystallization treatment in sequence; The conditions for the first crystallization treatment include: a temperature of 40~70℃ and a time of 24~96h; The conditions for the second stage of crystallization treatment include: a temperature of 70~150℃ and a time of 6~48h.

[0009] Optionally, the inorganic base containing a metal element includes sodium hydroxide and / or potassium hydroxide; Preferably, the inorganic alkali containing a metal element includes sodium hydroxide and potassium hydroxide, and in the mixture, K + / (K + +Na + The molar ratio of ) is 0.01~1.0, preferably 0.01~0.6; The silicon source includes one or more of water glass, sodium silicate, silica sol, silica, tetraethyl orthosilicate, and methyl orthosilicate; The aluminum source includes one or more of sodium aluminate, low-alkalinity sodium aluminate, boehmite, gibbsite, and aluminum isopropoxide.

[0010] Optionally, in step (1), the molar ratio of silicon (calculated as SiO2) to aluminum (calculated as Al2O3) in the mixture is (2.0~25.0):1, preferably (2.0~15.0):1; the molar ratio of inorganic alkali metal (calculated as metal oxide) to silicon (calculated as SiO2) is (0.6~1.8):1, preferably (1.0~1.5):1; and the molar ratio of H2O to aluminum (calculated as Al2O3) is (120.0~220.0):1, preferably (140.0~190.0):1.

[0011] Optionally, in step (1), the mixing is carried out under stirring conditions, including a temperature of 10~50℃ and a time of 0.5~3h.

[0012] Optionally, in step (2), the aging treatment conditions include: a temperature of 5~35℃ and a time of 6~36h.

[0013] Optionally, in step (3), the conditions for the first crystallization treatment include: a temperature of 50~60℃ and a time of 72~84h.

[0014] Optionally, in step (3), the conditions for the second crystallization process include: a temperature of 80~110℃ and a time of 12~24h.

[0015] The third aspect of this disclosure provides microporous-mesoporous X molecular sieves prepared using the method described in the second aspect of this disclosure.

[0016] The fourth aspect of this disclosure provides a method for adsorbing and separating p-xylene from a C8 mixed aromatic hydrocarbon. The method includes: contacting the C8 mixed aromatic hydrocarbon containing p-xylene with an adsorbent for adsorption to obtain an adsorbed molecular sieve containing p-xylene; the adsorbent includes the microporous-mesoporous X molecular sieve described in the first or third aspect of this disclosure.

[0017] Optionally, the adsorption conditions include: a pressure of 0.3~1.5MPa and a temperature of 120~190℃.

[0018] Optionally, the method further includes: contacting the molecular sieve that adsorbed p-xylene with a desorbent to desorb it; The desorbent includes p-ethylbenzene and / or toluene; The desorption conditions include: a pressure of 0.3~1.5MPa and a temperature of 120~190℃.

[0019] Optionally, the C8 mixed aromatics include ethylbenzene, p-xylene, m-xylene, and o-xylene.

[0020] Through the above technical solution, the method disclosed herein, by controlling specific crystallization steps and conditions, restricts the generation of EMT structures, preparing a molecular sieve comprising a structure of crystals formed by stacked nanoparticles, and exhibiting no EMT characteristic peaks in its XRD pattern, thus demonstrating good mass transfer performance. This molecular sieve possesses a FAU crystalline phase and a suitable pore distribution, containing multi-level microporous and mesoporous channels, which is beneficial for improving the mass transfer capacity and adsorption capacity of the molecular sieve. When used as an adsorbent for the adsorption and separation of C8 aromatic isomers, it can separate p-xylene, exhibiting high adsorption selectivity and mass transfer efficiency. The preparation method disclosed herein does not use a template agent, avoiding the calcination process of organic template agents, thus reducing the energy consumption and CO2 emissions in molecular sieve production. x and NO x It reduces greenhouse gas emissions and is more environmentally friendly.

[0021] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Attached Figure Description

[0022] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof. In the drawings: Figure 1 The XRD pattern of the microporous-mesoporous X molecular sieve prepared in Example 1 of this disclosure; Figure 2 SEM image of the microporous-mesoporous X molecular sieve prepared in Example 1 of this disclosure; Figure 3 The BJH pore size distribution curve of the microporous-mesoporous X molecular sieve prepared in Example 1 of this disclosure; Figure 4 The microporous-mesoporous X molecular sieve prepared in Example 1 of this disclosure 27 Al NMR spectrum; Figure 5 The microporous-mesoporous X molecular sieve prepared in Example 1 of this disclosure 29 Si NMR spectrum; Figure 6 SEM image of the microporous-mesoporous X molecular sieve prepared in Example 2 of this disclosure; Figure 7 This is a SEM image of the microporous-mesoporous X molecular sieve prepared in Example 3 of this disclosure; Figure 8 SEM image of the X molecular sieve prepared in Comparative Example 1 of this disclosure; Figure 9 This is a TEM image of the microporous-mesoporous X molecular sieve prepared in Example 1 of this disclosure; Figure 10This is a TEM image of the microporous-mesoporous X molecular sieve prepared in Example 1 of this disclosure. Detailed Implementation

[0023] The specific embodiments of this disclosure will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit this disclosure.

[0024] The first aspect of this disclosure provides a microporous-mesoporous X molecular sieve, wherein the microporous-mesoporous X molecular sieve comprises crystals formed by stacking nanoparticles; The microporous-mesoporous X molecular sieve includes the FAU crystalline phase, and the characteristic peaks of EMT are not present in the XRD pattern. In the microporous-mesoporous X molecular sieve, skeletal aluminum accounts for 90.0% to 99.0% of the total aluminum, and silicon with a chemical environment of Si(4Al, 0Si) accounts for 35.0% to 50.0% of the total silicon. The total pore volume of the X molecular sieve is 0.30~0.45 cm³. 3 / g, the proportion of mesopore volume to total pore volume is 3.0~50.0%, the proportion of micropore volume to total pore volume is 50.0~97.0%, the most probable pore size of mesopores is 2~15nm, and the specific surface area of ​​micropores is 720~760m². 2 / g, mesoporous specific surface area is 20~100m² 2 / g; The average grain size is 0.8~5.0 μm.

[0025] The microporous-mesoporous X-type molecular sieve disclosed herein comprises a FAU crystalline phase and exhibits no characteristic EMT peaks in its XRD pattern. Furthermore, the molecular sieve comprises crystallites formed by stacked nanoparticles, while maintaining appropriate aluminum and silicon coordination. Therefore, it possesses both high intracrystalline mass transfer capacity and adsorption performance, making it suitable for the adsorption and separation of C8 aromatic isomers.

[0026] According to one embodiment of this disclosure, the nanoparticles include nanosheets, which have a layered structure. The nanosheets have a dimension of 50-500 nm in the direction of the minimum dimension passing through the center, including but not limited to 50 nm, 60 nm, 70 nm, 75 nm, 80 nm, 90 nm, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, 220 nm, 250 nm, 300 nm, 350 nm, 400 nm, 420 nm, 480 nm, 500 nm, or any combination thereof. The direction of the minimum dimension passing through the center of the nanosheet is the thickness direction of the nanosheet. Figure 2 This is a SEM image of a microporous-mesoporous X molecular sieve according to one embodiment of this disclosure. Figure 2 The red short line in the figure exemplarily represents size L; “size L” refers to any size in the direction of the minimum size of the nanosheet passing through the center; perpendicular to the thickness direction is the sheet direction of the nanosheet, in which the minimum size of the nanosheet passing through the center is greater than 0.8 μm and the maximum size is less than 5.0 μm.

[0027] According to one embodiment of this disclosure, the nanoparticles include one or more of nanoparticles, nanowires, and nanorods; wherein, "nanoparticles" refers to particles whose three dimensions are all at the nanoscale, that is, any size passing through the center of the nanoparticle is at the nanoscale; "nanowires" refers to particles whose radial dimensions are at the nanoscale and whose aspect ratio is greater than 1000; "nanorods" refers to particles whose radial dimensions are at the nanoscale and whose aspect ratio is 10 to 100.

[0028] In this disclosure, the content of skeletal aluminum as a percentage of the total aluminum content and the content of silicon in a chemical environment of Si (4Al, 0Si) as a percentage of the total silicon content are determined by NMR spectroscopy.

[0029] According to one embodiment of this disclosure, in the microporous-mesoporous X molecular sieve, the proportion of skeletal aluminum to the total aluminum is including but not limited to 90.0%, 91.0%, 92.0%, 92.8%, 93.4%, 94.0%, 94.7%, 95.0%, 95.3%, 96.8%, 97.2%, 97.6%, 98.1%, 98.2%, 98.8%, 99.0%, or any combination thereof.

[0030] According to one embodiment of this disclosure, in the microporous-mesoporous X molecular sieve, the proportion of silicon with a chemical environment of Si (4Al, 0Si) to the total silicon includes, but is not limited to, 35.0%, 36.0%, 36.6%, 37.9%, 38.2%, 39.0%, 39.8%, 40.3%, 41.7%, 42.9%, 43.0%, 43.7%, 44.0%, 44.8%, 45.7%, 46.0%, 46.9%, 47.2%, 48.0%, 48.6%, 49.1%, 50.0%, or any combination thereof.

[0031] According to one embodiment of this disclosure, the total pore volume of the X molecular sieve includes, but is not limited to, 0.30 cm³. 3 / g, 0.31 cm 3 / g, 0.32 cm 3 / g, 0.35 cm 3 / g, 0.37 cm 3 / g, 0.38 cm 3 / g, 0.40 cm3 / g, 0.42 cm 3 / g, 0.45 cm 3 / g, or a range of values ​​consisting of any two of them.

[0032] According to one embodiment of this disclosure, the proportion of mesopore volume to total pore volume is 10.0% to 50.0%, including but not limited to 10.0%, 12.0%, 15.0%, 17.5%, 18.0%, 20.0%, 21.0%, 22.0%, 23.5%, 25%, 30.0%, 35.0%, 37.5%, 40.0%, 45.0%, 50.0%, or any combination thereof; the proportion of micropore volume to total pore volume is 50.0% to 90.0%, including but not limited to 50.0%, 55.0%, 60.0%, 65.0%, 70.0%, 72.5%, 75.0%, 77.0%, 80.0%, 85.0%, 90.0%, or any combination thereof.

[0033] According to one embodiment of this disclosure, the most probable pore size of the mesopore includes, but is not limited to, 2 nm, 3 nm, 5 nm, 6.9 nm, 7 nm, 7.5 nm, 7.8 nm, 8.0 nm, 8.5 nm, 9 nm, 9.1 nm, 9.7 nm, 10 nm, 10.5 nm, 11 nm, 11.5 nm, 12 nm, 12.7 nm, 13 nm, 13.5 nm, 14 nm, 14.5 nm, 15 nm, or a range of any two of these.

[0034] According to one embodiment of this disclosure, the specific surface area of ​​the micropores includes, but is not limited to, 720 m². 2 / g、725 m 2 / g、730m 2 / g、735 m 2 / g、738 m 2 / g、740 m 2 / g、745 m 2 / g、750 m 2 / g、752 m 2 / g、755 m 2 / g、760 m 2 / g, or a range of values ​​consisting of any two of them.

[0035] According to one embodiment of this disclosure, the mesoporous specific surface area includes, but is not limited to, 20 m². 2 / g、22 m 2 / g、25m 2 / g、28 m 2 / g、30 m 2 / g、32 m 2 / g、35 m 2 / g、38 m 2 / g、40 m 2 / g、45 m 2 / g、50 m 2 / g、52 m 2 / g、55m 2 / g、60 m 2 / g、65 m 2 / g、67 m 2 / g、70 m 2 / g、75 m 2 / g、80 m 2 / g、85 m 2 / g、90 m 2 / g、92 m 2 / g、97m 2 / g、100 m 2 / g, or a range of values ​​consisting of any two of them.

[0036] According to one embodiment of this disclosure, the average grain size of the grains includes, but is not limited to, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.9 μm, 2.0 μm, 2.2 μm, 2.5 μm, 2.7 μm, 3.0 μm, 3.2 μm, 3.5 μm, 3.7 μm, 4.0 μm, 4.5 μm, 4.7 μm, 5.0 μm, or any combination thereof.

[0037] According to one embodiment of this disclosure, in the microporous-mesoporous X molecular sieve, the molar ratio of silicon (calculated as SiO2) to aluminum (calculated as Al2O3) is 1.0 to 3.0, preferably 2.2 to 2.8.

[0038] According to one embodiment of this disclosure, the cations in the microporous-mesoporous X molecular sieve include Na. + and / or K + In the microporous-mesoporous X molecular sieve, the total content of Na2O and K2O is 18.0~20.0 by weight.

[0039] A second aspect of this disclosure provides a method for preparing microporous-mesoporous X molecular sieves, the method comprising: (1) Mix an inorganic alkali containing metal elements, a silicon source, an aluminum source, and water to obtain a mixture; (2) The mixture is subjected to aging treatment to obtain an aging product; (3) The aging products are subjected to a first-stage crystallization treatment and a second-stage crystallization treatment in sequence; The conditions for the first crystallization treatment include: a temperature of 40~70℃ and a time of 24~96h; The conditions for the second stage of crystallization treatment include: a temperature of 70~150℃ and a time of 6~48h.

[0040] The inventors of this disclosure, through extensive research, discovered that controlling the crystallization steps and conditions without adding any organic template agent can limit the formation of EMT structures, synthesizing X-type molecular sieves with pure FAU crystalline phases possessing micropores and mesopores. By controlling the conditions of the first-stage crystallization, the crystal structure of the molecular sieve can be controlled, which is beneficial to improving the intracrystalline mass transfer capacity of the molecular sieve. Then, by controlling the conditions of the second-stage crystallization, the molecular sieve can possess high micropore volume and considerable adsorption capacity. The preparation method of this disclosure does not require the addition of organic template agents, thereby avoiding the calcination step required to eliminate organic template agents, effectively reducing energy consumption in the molecular sieve production process, and reducing greenhouse gas emissions such as COx and NOx, exhibiting higher environmental friendliness and green production characteristics.

[0041] According to one embodiment of this disclosure, in step (1), the molar ratio of silicon (calculated as SiO2) to aluminum (calculated as Al2O3) in the mixture is (2.0~25.0):1, preferably (2.0~15.0):1, including but not limited to 2.0:1, 2.8:1, 2.85:1, 3.0:1, 5.0:1, 8.0:1, 10:1, 15:1, 20:1, 25:1, or any combination thereof; the molar ratio of inorganic alkali metal (calculated as metal oxide) to silicon (calculated as SiO2) is (0.6~1.8):1, preferably (1.0~1.5):1, 0.6:1, 1.0:1, 1.2:1, 1.33:1, 1.5:1, 1.65:1. The ratio of H2O to aluminum (calculated as Al2O3) is 1.8:1, or any combination thereof; the molar ratio of H2O to aluminum is (120.0~220.0):1, preferably (140.0~190.0):1, including but not limited to 120.0:1, 130.0:1, 140.0:1, 150.0:1, 160.0:1, 165.0:1, 170.0:1, 180.0:1, 185.0:1, 190.0:1, 200.0:1, 220.0:1, or any combination thereof, wherein the inorganic alkali metal element does not include aluminum, and the inorganic alkali containing the metal element is selected from sodium hydroxide and / or potassium hydroxide, and the inorganic alkali metal element containing the metal element includes sodium and / or potassium. In the above embodiments, by selecting the preferred feed amount, it is beneficial to synthesize an X molecular sieve synthesis system with a suitable structure.

[0042] According to one embodiment of the present disclosure, in step (1), the inorganic alkali containing metal elements, the silicon source, and the aluminum source are all added in the form of a solution. Specifically, step (1) includes: mixing the solution of the inorganic alkali containing metal elements, the silicon source solution, the aluminum source solution, and optional water to obtain a mixture.

[0043] According to one embodiment of this disclosure, the inorganic base containing a metal element includes sodium hydroxide and / or potassium hydroxide; preferably, the inorganic base containing a metal element includes sodium hydroxide and potassium hydroxide, wherein in the mixture, K + / (K + +Na + The molar ratio of ) is 0.01~1.0, preferably 0.01~0.6. By adopting the above embodiment, the adsorption selectivity of molecular sieve for C8 aromatic isomers can be improved while ensuring that the molecular sieve has high adsorption capacity and mass transfer performance.

[0044] According to one embodiment of this disclosure, the silicon source includes one or more of water glass, sodium silicate, silica sol, silica fume, tetraethyl orthosilicate, and methyl orthosilicate. When the silicon source includes two or more, this disclosure does not impose specific restrictions on their proportions. The silicon source preferably includes water glass and / or sodium silicate. The aluminum source includes one or more of sodium aluminate, low-alkalinity sodium aluminate, boehmite, gibbsite, and aluminum isopropoxide. The low-alkalinity sodium aluminate is an aqueous solution containing sodium hydroxide and sodium aluminate. Its composition can be, for example, 14.90% by weight of Na (calculated as Na2O), 13.62% by weight of Al (calculated as Al2O3), and 71.48% by weight of water. When the aluminum source includes two or more, this disclosure does not impose specific restrictions on their proportions. The aluminum source is preferably low-alkalinity sodium aluminate.

[0045] According to one embodiment of this disclosure, in step (1), the mixing is carried out under stirring conditions, including: a temperature of 10~50℃, preferably 10~30℃, including but not limited to 10℃, 20℃, 25℃, 28℃, 30℃, 35℃, 40℃, 42℃, 45℃, 50℃, or any combination thereof; and a time of 0.5~3h, preferably 0.5~1.5h, including but not limited to 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, or any combination thereof.

[0046] According to one embodiment of this disclosure, in step (2), the aging treatment conditions include: a temperature of 5~35℃, including but not limited to 5℃, 8℃, 10℃, 20℃, 25℃, 28℃, 30℃, 35℃, or any combination thereof; and a time of 6~36h, including but not limited to 6h, 7h, 10h, 12h, 20h, 25h, 30h, 36h, or any combination thereof. In the above embodiment, by selecting preferred aging conditions, the dissolution and mixing of aluminosilicates in the X molecular sieve synthesis system are promoted, which is conducive to the more complete growth and more orderly directional arrangement of molecular sieve crystals, so that the molecular sieve has higher crystallinity and adsorption capacity.

[0047] According to one embodiment of this disclosure, in step (3), the conditions for the first crystallization treatment include: a temperature of 50~60℃ and a time of 72~84h; the crystallization time includes, but is not limited to, 40℃, 42℃, 45℃, 48℃, 50℃, 55℃, 60℃, 62℃, 65℃, 70℃, or any combination thereof; the crystallization time includes, but is not limited to, 24h, 30h, 32h, 36h, 40h, 42h, 48h, 56h, 60h, 65h, 72h, 80h, 84h, 96h, or any combination thereof. In the above embodiments, by selecting preferred crystallization conditions, it is beneficial to limit the formation of EMT structures.

[0048] According to one embodiment of this disclosure, in step (3), the conditions for the second crystallization treatment include: a temperature of 80~110℃ and a time of 12~24h; the crystallization time includes, but is not limited to, 70℃, 72℃, 75℃, 78℃, 80℃, 85℃, 90℃, 100℃, 120℃, 130℃, 140℃, 150℃, or any combination thereof; the crystallization time includes, but is not limited to, 6h, 8h, 10h, 12h, 15h, 20h, 24h, 30h, 36h, 42h, 48h, or any combination thereof. In the above embodiment, by selecting preferred crystallization conditions, the FAU structure grains are further crystallized completely, resulting in a microporous-mesoporous X molecular sieve with high adsorption capacity and high crystallinity. The mesopores in this type of molecular sieve can improve the mass transfer performance of C8 aromatics, while also having more micropores and cation exchange sites, thus exhibiting higher adsorption and separation rates, adsorption capacity and selectivity for C8 aromatics.

[0049] According to one embodiment of this disclosure, the method further includes: performing solid-liquid separation on the mixture obtained from the second crystallization treatment, washing the obtained solid with deionized water until the pH of the filtrate is neutral, and then drying it. The solid-liquid separation includes one or more of filtration, vacuum filtration, centrifugation, and rotary evaporation, preferably vacuum filtration. The drying conditions include: a temperature of 50~120℃, preferably 50~90℃; a time of 2~48 h, preferably 2~24 h. The drying method is conventional in the art and is not specifically limited by this disclosure.

[0050] The third aspect of this disclosure provides microporous-mesoporous X molecular sieves prepared using the method described in the second aspect of this disclosure.

[0051] The microporous-mesoporous X molecular sieve described in the third aspect of this disclosure has the same characteristics as the microporous-mesoporous X molecular sieve described in the first aspect of this disclosure, and will not be described again here.

[0052] The fourth aspect of this disclosure provides a method for adsorbing and separating p-xylene from a C8 mixed aromatic hydrocarbon. The method includes: contacting the C8 mixed aromatic hydrocarbon containing p-xylene with an adsorbent for adsorption to obtain an adsorbed molecular sieve containing p-xylene; the adsorbent includes the microporous-mesoporous X molecular sieve described in the first or third aspect of this disclosure.

[0053] In this disclosure, the microporous-mesoporous X molecular sieve has a suitable microporous and intracrystalline mesoporous structure and a high adsorption capacity, for example, the toluene adsorption capacity is above 233 mg / g; when used for the adsorption and separation of C8 mixed aromatics, it is beneficial to improve the adsorption and separation performance and the adsorption selectivity for xylene.

[0054] According to one embodiment of this disclosure, the adsorption conditions include: a pressure of 0.3~1.5 MPa, including but not limited to 0.3 MPa, 0.5 MPa, 0.8 MPa, 1.0 MPa, 1.0 MPa, 1.5 MPa, or any combination thereof; and a temperature of 120~190℃, including but not limited to 120℃, 150℃, 177℃, 190℃, or any combination thereof.

[0055] According to one embodiment of this disclosure, the method further includes: contacting the molecular sieve adsorbed with p-xylene with a desorbent for desorption; the desorbent includes p-diethylbenzene and / or toluene; the desorption conditions include: a pressure of 0.3~1.5 MPa, including but not limited to 0.3 MPa, 0.5 MPa, 0.8 MPa, 1.0 MPa, 1.0 MPa, 1.5 MPa, or any combination thereof; and a temperature of 120~190℃, including but not limited to 120℃, 150℃, 177℃, 190℃, or any combination thereof.

[0056] According to one embodiment of this disclosure, the C8 mixed aromatics include ethylbenzene (EB), p-xylene (PX), m-xylene (MX) and o-xylene (OX), wherein the content of p-xylene (PX) is 5-30% by volume.

[0057] The present disclosure will be further illustrated by the following examples, but the present disclosure is not limited thereto.

[0058] In the embodiments and comparative examples of this disclosure, the total pore volume, micropore volume, mesopore volume, specific surface area, and pore size distribution of the molecular sieve were determined by nitrogen physical adsorption method. The testing instrument was a Micromeritics ASAP2020 physical adsorption instrument. Before testing, the samples were subjected to nitrogen adsorption at 300-450°C and under vacuum (<10). -2 Degassing was performed at 300℃ for 6.0-16.0 h under conditions of 0.1 MPa, preferably at 300℃ for 10.0 h. Nitrogen physical adsorption was carried out at 77 K. The total specific surface area and average adsorption pore size of the molecular sieve were calculated using the BET (Brunauer-Emmett-Teller) equation; the total pore volume of the sample was determined by the amount of nitrogen adsorbed when P0 was 0.1 MPa and the relative adsorption capacity P / P0 = 0.975. The micropore surface area, external specific surface area, and micropore volume were calculated using the t-plot method. The pore size distribution of micropores and mesopores was calculated using the Barrett-Joyner-Halenda method.

[0059] The crystal structure of the molecular sieve was determined using X-ray diffraction (XRD) on a PANalytical-XPert diffractometer in the Netherlands. The sample was ground to <200 mesh and then laid flat on a specially designed glass support for testing. The radiation source was CuKα (λ=0.154nm), the operating voltage was 40kV, the operating current was 40mA, the scanning range was 5°–35°, and the scanning rate was 4° / min.

[0060] The contents of Na2O and K2O, as well as the contents of SiO2 and Al2O3 in the molecular sieve were determined using a Rigaku Electric Co., Ltd. 3013 X-ray fluorescence spectrometer, and the silicon-to-aluminum ratio of the molecular sieve was calculated.

[0061] The size and morphology of the molecular sieve crystallites were characterized using FE-SEM and HR-TEM images. For FE-SEM, a Hitachi S-4800 scanning electron microscope (Japan) was used, and the crystallite size within a range of 10.0 μm × 10.0 μm was measured and calculated; the measured crystallite size was the average of all crystallites. For HR-TEM, a Tecnai G2 F20 S-TWIN high-resolution transmission electron microscope (FEI) was used, and the crystallite size within a range of 0.5 μm × 0.5 μm was measured and calculated; the measured crystallite size was the average of all crystallites.

[0062] The coordination number and existing forms of silicon and aluminum atoms in molecular sieves are used 29 Si and 27 Al high-resolution magic angle nuclear magnetic resonance (MAS NMR) characterization, 29 Si nucleus and 27 Single-pulse spectra of Al nuclei were obtained using a Bruker Avance III 500 WB spectrometer. 29 Si nucleus and 27 The resonance frequencies of the Al core are 500.1 MHz and 89.6 MHz, respectively.

[0063] Example 1 (1) 48.10g of water glass (silicon source, the Si content in the water glass is SiO2, the mass fraction is 19.85 wt%, the Na content is Na2O, the mass fraction is 6.30 wt%, and the mass fraction of water is 73.95 wt%), 41.61g of low-alkalinity sodium aluminate (aluminum source, the Na content is Na2O, the mass fraction is 14.90 wt%, the Al content is Al2O3, the mass fraction is 13.62 wt%, and the mass fraction of water is 71.48 wt%), 4.98g of sodium hydroxide (inorganic alkali, the Na content is Na2O, the mass fraction is 77.5 wt%, and the mass fraction of water is 22.5 wt%) and 83.57g of deionized water were added to a reaction vessel and stirred for 1 hour at a temperature of 30°C to obtain a mixture. In the mixture, the molar ratio of silicon (calculated as SiO2) to aluminum (calculated as Al2O3) is 2.85:1, the molar ratio of sodium (calculated as Na2O) to silicon (calculated as SiO2) is 1.33:1, and the molar ratio of H2O to aluminum (calculated as Al2O3) is 150.0:1. (2) Transfer the mixture prepared in step (1) into a closed reactor and age it at 35°C for 12 h to obtain the aged product; (3) The aging product prepared in step (2) was subjected to a first-stage crystallization treatment at 60°C for 72 h to obtain the first-stage crystallization product; (4) The first crystallization product prepared in step (3) was placed at 95°C for a second crystallization treatment for 24 h. After crystallization, solid-liquid separation was performed by vacuum filtration. The obtained solid was washed with deionized water until the pH of the filtrate was neutral. It was then dried at 90°C for 12 h to obtain microporous-mesoporous X molecular sieve, denoted as A1. Its structural characteristics are shown in Tables 1 and 2.

[0064] The XRD pattern of the obtained A1 is shown in the figure. Figure 1 See SEM Figure 2 The BJH aperture distribution curve is shown in [reference needed]. Figure 3 , 27 The Al NMR spectrum is shown below. Figure 4 , 29 See the Si NMR spectrum. Figure 5 TEM Figure 9 and 10 .

[0065] from Figure 1 It can be seen that the XRD pattern of A1 has peaks near 2θ=6.1°, 10.1°, 11.7°, 15.4°, 18.5°, 20.1°, 23.3°, 26.7°, and 30.9°, indicating that A1 is a pure FAU crystalline phase X molecular sieve and does not have an EMT structure. from Figure 2 , 9 As can be seen from 10, A1 has a nanosheet-like stacked grain morphology. Figure 2 Within several fields of view, 100 nanosheets were selected respectively, and the size L of the nanosheets was measured; from Figure 3 It can be seen that A1 has obvious mesoporous distribution peaks; Depend on Figure 4 After data fitting and calculation, it can be seen that A1's 27 The peak area of ​​framework aluminum at a chemical shift of 63 ppm in the Al NMR spectrum accounts for a significant portion of the total aluminum species. 27 98.2% of the area of ​​the Al peak is due to Figure 5 After data fitting and calculation, it can be seen that A1's 29 The peak area of ​​silicon species with a chemical environment of Si(4Al, 0Si) at a chemical shift of -85 ppm in the Si NMR spectrum accounts for the majority of the total silicon species peak area. 29 The area of ​​the Si peak is 45.7%.

[0066] Example 2 Microporous-mesoporous X molecular sieve A2 was prepared using the same steps as in Example 1, except that: in the mixture of step (1), the molar ratio of H2O to aluminum (calculated as Al2O3) was 180.0:1, and the temperature in the first crystallization process of step (3) was 50℃. Finally, microporous-mesoporous X molecular sieve A2 was obtained, and its structural characteristics are shown in Tables 1 and 2.

[0067] The SEM image of A2 is shown below. Figure 6 ,from Figure 6 It can be seen that A2 has a nanosheet stacked grain morphology. In several fields of view, 100 nanosheets were selected respectively, and the size L of the nanosheets was measured.

[0068] The XRD pattern of A2 shows peaks near 2θ = 6.1°, 10.1°, 11.8°, 15.5°, 18.5°, 20.1°, 23.4°, 26.7°, and 30.8°, indicating that A2 is a pure FAU crystalline phase X-zeel and does not possess an EMT structure. The pore size distribution diagram shows that A2 exhibits obvious mesoporous peaks; for A2... 27 After fitting and calculating the Al NMR spectrum, it can be seen that... 27 The peak area of ​​framework aluminum at a chemical shift of 63 ppm in the Al NMR spectrum accounts for a significant portion of the total aluminum species. 27 The area of ​​the Al peak is 97.6%; for A2... 29 After fitting and calculating the Si NMR spectrum, it can be seen that... 29 The peak area of ​​silicon species with a chemical environment of Si(4Al, 0Si) at a chemical shift of -85 ppm in the Si NMR spectrum accounts for the majority of the total area. 29 The area of ​​the Si peak is 43.7%.

[0069] Example 3 Microporous-mesoporous X molecular sieve A3 was prepared using the same steps as in Example 1, except that: in the mixture of step (1), the molar ratio of H2O to aluminum (calculated as Al2O3) was 200.0:1, and the temperature in the first crystallization process of step (3) was 70℃. Finally, microporous-mesoporous X molecular sieve A3 was obtained, and its structural characteristics are shown in Tables 1 and 2.

[0070] The SEM image of A3 is shown below. Figure 7 ,from Figure 7 It can be seen that A3 has a nanosheet stacked grain morphology. In several fields of view, 100 nanosheets were selected respectively, and the size L of the nanosheets was measured.

[0071] The XRD pattern of A3 shows peaks near 2θ = 6.1°, 10.1°, 11.7°, 15.5°, 18.5°, 20.1°, 23.3°, 26.7°, and 30.8°, indicating that A3 is a pure FAU crystalline phase X-zeel and does not possess an EMT structure. The pore size distribution diagram shows that A3 exhibits obvious mesoporous peaks; for A3... 27 After fitting and calculating the Al NMR spectrum, it can be seen that... 27 The peak area of ​​framework aluminum at a chemical shift of 63 ppm in the Al NMR spectrum accounts for a significant portion of the total aluminum species. 27 The area of ​​the Al peak is 98.8%; for A3 29 After fitting and calculating the Si NMR spectrum, it can be seen that... 29 The peak area of ​​silicon species with a chemical environment of Si(4Al, 0Si) at a chemical shift of -85 ppm in the Si NMR spectrum accounts for the majority of the total silicon species peak area. 29 The area of ​​the Si peak is 48.6%.

[0072] Example 4 Microporous-mesoporous X molecular sieve A4 was prepared using the same steps as in Example 1, except that in step (1), the inorganic base containing metal elements was a mixture of 4.98g sodium hydroxide and potassium hydroxide, and the microporous-mesoporous X molecular sieve A4 was finally obtained. Its structural characteristics are shown in Tables 1 and 2. In the mixture, the molar ratio of silicon (SiO2) to aluminum (Al2O3) is 2.85:1; the total molar ratio of sodium and potassium (Na2O and K2O) to silicon (SiO2) is 1.33:1; the molar ratio of H2O to aluminum (Al2O3) is 150.0:1; and K... + / (K + +Na + The molar ratio of ) is 0.2; The XRD pattern of A4 shows peaks near 2θ = 6.1°, 10.0°, 11.7°, 15.4°, 18.5°, 20.1°, 23.3°, 26.7°, and 30.9°, indicating that A4 is a pure FAU crystalline phase X-zeel and does not possess an EMT structure. SEM reveals that A4 has a nanosheet-like stacked grain morphology. The size L of 100 nanosheets was measured in several fields of view. The pore size distribution diagram shows that A4 exhibits obvious mesoporous distribution peaks. 27 After fitting and calculating the Al NMR spectrum, it can be seen that... 27 The peak area of ​​framework aluminum at a chemical shift of 63 ppm in the Al NMR spectrum accounts for a significant portion of the total aluminum species. 27 The area of ​​the Al peak is 98.1%; for A4 29 After fitting and calculating the Si NMR spectrum, it can be seen that... 29The peak area of ​​silicon species with a chemical environment of Si(4Al, 0Si) at a chemical shift of -85 ppm in the Si NMR spectrum accounts for the majority of the total silicon species peak area. 29 The area of ​​the Si peak is 44.8%.

[0073] Example 5 Microporous-mesoporous X molecular sieve A5 was prepared using the same steps as in Example 1, except that in step (2), the aging temperature was 25°C and the aging time was 18 h, and the microporous-mesoporous X molecular sieve A5 was finally obtained. Its structural characteristics are shown in Tables 1 and 2.

[0074] The XRD pattern of A5 shows peaks near 2θ = 6.1°, 10.1°, 11.7°, 15.5°, 18.5°, 20.1°, 23.3°, 26.7°, and 30.8°, indicating that A5 is a pure FAU crystalline phase X-zeel and does not possess an EMT structure. SEM reveals that A5 has a nanosheet-like stacked grain morphology. The size L of 100 nanosheets was measured in several fields of view. The pore size distribution diagram shows that A5 exhibits obvious mesoporous distribution peaks. 27 After fitting and calculating the Al NMR spectrum, it can be seen that... 27 The peak area of ​​framework aluminum at a chemical shift of 63 ppm in the Al NMR spectrum accounts for the total area of ​​the total. 27 The area of ​​the Al peak is 97.2%; for A5 29 After fitting and calculating the Si NMR spectrum, it can be seen that... 29 The peak area of ​​silicon species with a chemical environment of Si(4Al, 0Si) at a chemical shift of -85 ppm in the Si NMR spectrum accounts for the majority of the total silicon species peak area. 29 The area of ​​the Si peak is 42.9%.

[0075] Example 6 Microporous-mesoporous X molecular sieve A6 was prepared using the same steps as in Example 1, except that: in the first crystallization process of step (3), the crystallization temperature was 40℃ and the crystallization time was 96h, and the microporous-mesoporous X molecular sieve A6 was finally obtained. Its structural characteristics are shown in Tables 1 and 2.

[0076] The XRD pattern of A6 shows peaks near 2θ = 6.1°, 10.0°, 11.7°, 15.4°, 18.5°, 20.1°, 23.3°, 26.7°, and 30.9°, indicating that A6 is a pure FAU crystalline phase X-zeel and does not possess an EMT structure. SEM reveals that A6 has a nanosheet-like stacked grain morphology. The size L of 100 nanosheets was measured in several fields of view. The pore size distribution diagram shows that A6 exhibits obvious mesoporous distribution peaks. 27 After fitting and calculating the Al NMR spectrum, it can be seen that... 27The peak area of ​​framework aluminum at a chemical shift of 63 ppm in the Al NMR spectrum accounts for a significant portion of the total aluminum species. 27 The area of ​​the Al peak is 94.7%; for A6 29 After fitting and calculating the Si NMR spectrum, it can be seen that... 29 The peak area of ​​silicon species with a chemical environment of Si(4Al, 0Si) at a chemical shift of -85 ppm in the Si NMR spectrum accounts for the majority of the total silicon species peak area. 29 The area of ​​the Si peak is 39.8%.

[0077] Comparative Example 1 (1) 23.61g of water glass (first silicon source, the Si content in water glass is SiO2, the mass fraction is 19.85 wt%, the Na content is Na2O, the mass fraction is 6.25 wt%, the mass fraction of water is 73.90 wt%, the same below), 2.53g of low alkalinity sodium aluminate (first aluminum source, the Na content is Na2O, the mass fraction is 22.97 wt%, the Al content is Al2O3, the mass fraction is 20.99 wt%, the mass fraction of water is 56.04 wt%), 4.01g of sodium hydroxide (first inorganic base, the Na content is Na2O, the mass fraction is 77.5 wt%, the mass fraction of water is 22.5 wt%) and 10.23g of deionized water were added to the reaction vessel and mixed evenly to obtain a mixture. Then the mixture was placed in a constant temperature bath at 35℃ for 24h to age and obtain the aged product. In the mixture, the molar ratio of silicon (calculated as SiO2) to aluminum (calculated as Al2O3) is 15:1, the molar ratio of sodium (calculated as Na2O) to silicon (calculated as SiO2) is 1.07:1, and the molar ratio of H2O to aluminum (calculated as Al2O3) is 21.3:1. (2) 2.87g sodium hydroxide (second inorganic base), 41.77g water glass (second silicon source), and 103.53g deionized water were stirred thoroughly at 25°C. 24.57g sodium aluminate (second aluminum source) was added while stirring and mixed well. Then, 0.36g of the aging product from step (1) was added and stirred evenly. 0.57g of a 60% by mass aqueous solution of dimethylhexadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (template solution, denoted as R, chemical formula [(CH3O)3Si(CH2)3N(CH3)2(CH2)) was added. 15 [CH3Cl], R to SiO2 mass ratio is 0.01), continue stirring until uniformly mixed to obtain the second mixture; In the second mixture, the molar ratio of silicon (SiO2) to aluminum (Al2O3) is 3.0:1, the molar ratio of inorganic alkali metals (Na2O) to silicon (SiO2) is 1.2:1, and the molar ratio of H2O to aluminum (Al2O3) is 60.0:1; the amount of Al2O3 contained in the added aging product accounts for 0.15% of the total Al2O3 contained in the second mixture. (3) The second mixture prepared in step (2) was transferred to a closed reaction vessel and hydrothermally crystallized at 95°C for 48 hours. After crystallization, solid-liquid separation was carried out by vacuum filtration. The obtained solid was washed with deionized water until the pH of the filtrate was neutral. It was then dried at 90°C for 12 hours to obtain microporous-mesoporous X molecular sieve, denoted as D1. Its structural characteristics are shown in Tables 1 and 2.

[0078] The XRD pattern of D1 shows peaks near 2θ = 6.3°, 10.3°, 12.1°, 15.8°, 18.7°, 20.4°, 23.8°, 27.1°, and 30.2°, indicating that D1 is a pure FAU crystalline phase X-zeel; the SEM image of D1 is shown in [image missing]. Figure 8 ,from Figure 8 It can be seen that D1 does not have a nanosheet-like stacked grain morphology; the pore size distribution diagram shows that D1 has obvious mesoporous distribution peaks; regarding D1... 27 After fitting and calculating the Al NMR spectrum, it can be seen that... 27 The peak area of ​​framework aluminum at a chemical shift of 63 ppm in the Al NMR spectrum accounts for a significant portion of the total aluminum species. 27 The area of ​​the Al peak is 96.5%; for D1 29 After fitting and calculating the Si NMR spectrum, it can be seen that... 29 In the Si NMR spectrum, the peak area of ​​silicon species with a chemical environment of Si (4Al, 0Si) at a chemical shift of -85 ppm accounts for 41.7% of the total silicon species.

[0079] Comparative Example 2 (1) Dissolve 1202.54g of sodium aluminate (the first aluminum source, in which the Na content is calculated as Na2O with a mass fraction of 31.54 wt% and the Al content is calculated as Al2O3 with a mass fraction of 38.54 wt%) in 4000.0g of deionized water and stir until completely dissolved. Then add 990.0g of KOH and 1284.18g of NaOH and mix evenly. Next, add 2519.26g of water glass (the first silicon source, in which the Na content is calculated as Na2O with a mass fraction of 7.35 wt%, the Si content is calculated as SiO2 with a mass fraction of 23.85 wt%, and the water mass fraction is 68.80 wt%) and add 3725.98g of water. Deionized water forms a gel with a molar ratio of Na2O:K2O:SiO2:Al2O3:H2O = 5.5:1.65:2.2:1.0:122. The mixed gel is then aged at 70℃ for 3 hours and then heated to 100℃ for 2 hours to crystallize. (2) Weigh 9097.69g of silica sol (second silicon source, where Na content is calculated as Na2O with a mass fraction of 0.24 wt% and Si content is calculated as SiO2 with a mass fraction of 30.38 wt%), 714.97g of aluminum hydroxide (second aluminum source, dry basis 65.60 wt%), 863.58g of sodium hydroxide, 429.85g of 18-crown-6, and 5021.14g of deionized water and mix thoroughly and evenly. The molar composition of the prepared mixed gel is N a2O:SiO2:Al2O3:(18-Crown-6):H2O=2.4:10.0:1.0:0.35:140. The gel was aged at room temperature for 24 hours with stirring. The crystallized product obtained in (1) was added to it and stirred and mixed evenly. Then it was transferred to a stainless steel autoclave Teflon inner liner and crystallized at 110°C for 10 days. The filter cake was recovered by vacuum filtration and washed with deionized water until the pH value was 8.0. After drying, the comparative X molecular sieve was obtained and denoted as D2. Its structural characteristics are shown in Tables 1 and 2.

[0080] The XRD pattern of D2 shows peaks near 2θ = 5.9°, 6.3°, 6.6°, 8.6°, 10.3°, 11.0°, 12.0°, 16.0°, 19.0°, 22.7°, 23.4°, 24.0°, and 27.5°, indicating that D2 is an X-ray molecular sieve with a coexisting FAU / EMT crystalline phase. SEM analysis shows that D2 does not exhibit a nanosheet-like stacked crystal morphology; the pore size distribution map shows that D2 has obvious mesoporous distribution peaks; regarding D2... 27 After fitting and calculating the Al NMR spectrum, it can be seen that... 27 The peak area of ​​framework aluminum at a chemical shift of 63 ppm in the Al NMR spectrum accounts for a significant portion of the total aluminum species. 27 The area of ​​the Al peak is 61.1%; compared to D2 29After fitting and calculating the Si NMR spectrum, it can be seen that... 29 In the Si NMR spectrum, the peak area of ​​silicon species with a chemical environment of Si (4Al, 0Si) at a chemical shift of -85 ppm accounts for 25.6% of the total silicon species.

[0081] Comparative Example 3 (1) Under stirring conditions, 4.02 kg of sodium hydroxide, 10.90 kg of deionized water, 2.22 kg of low-alkalinity sodium aluminate (aluminum source, where the Na content is calculated as Na2O with a mass fraction of 26.09 wt%, the Al content is calculated as Al2O3 with a mass fraction of 23.93 wt%, and the water mass fraction is 49.98 wt%) and 23.24 kg of water glass (silicon source, where the Na content is calculated as Na2O with a mass fraction of 6.32%, the Si content is calculated as SiO2 with a mass fraction of 20.17%, and the water mass fraction is 73.51%) were added to the reactor. The molar ratio of each material was SiO2 / Al2O3 = 15, Na2O / SiO2 = 1.07, and H2O / SiO2 = 21. The mixture was then aged at 35°C for 16 h to obtain the directing agent.

[0082] (2) Cool water glass and low-alkalinity sodium aluminate to 0℃ respectively.

[0083] (3) Under stirring conditions, 8.17 kg of deionized water, 3.67 kg of potassium hydroxide, 46.94 kg of low-alkalinity sodium aluminate cooled to 0°C in step (2), 91.32 kg of water glass cooled to 0°C in step (2), and 0.85 kg of the directing agent prepared in step (1) were added to the reactor to obtain the X molecular sieve synthesis system, wherein the molar ratio of each material was SiO2 / Al2O3=2.80, (Na2O+K2O) / SiO2=1.05, H2O / SiO2=18, K + / (K + +Na + =0.1, the molar ratio of Al2O3 contained in the directing agent to Al2O3 contained in the X molecular sieve synthesis system is 0.10%, and the temperature of the synthesis system is 3℃.

[0084] (4) The X molecular sieve synthesis system obtained in step (3) was transferred to a closed reaction vessel, heated to 100°C and statically crystallized for 2 hours, stirred for 5 minutes, and statically crystallized for another 10 hours. Then it was filtered, and the obtained solid was washed with deionized water until the pH of the filtrate was 8~9. It was dried at 80°C for 12 hours to obtain the comparative X molecular sieve, denoted as D3. Its structural characteristics are shown in Tables 1 and 2.

[0085] The XRD pattern of D3 shows peaks near 2θ = 6.3°, 10.3°, 12.1°, 15.8°, 18.7°, 20.4°, 23.8°, 27.1°, and 30.2°, indicating that D3 is a pure FAU crystalline phase X-zeel. SEM analysis shows that D3 does not exhibit a nanosheet-like stacked crystal morphology. The pore size distribution diagram shows that D3 has two distinct mesoporous peaks. Regarding D3... 27 After fitting and calculating the Al NMR spectrum, it can be seen that... 27 The peak area of ​​framework aluminum at a chemical shift of 63 ppm in the Al NMR spectrum accounts for a significant portion of the total aluminum species. 27 The area of ​​the Al peak is 86.7%; for D3 29 After fitting and calculating the Si NMR spectrum, it can be seen that... 29 In the Si NMR spectrum, the peak area of ​​silicon species with a chemical environment of Si (4Al, 0Si) at a chemical shift of -85 ppm accounts for 33.5% of the total silicon species.

[0086] Comparative Example 4 Add 15.0g of an aqueous solution of silane coupling agent (KH550) to 400.0g of water glass, add 150.0g of water, and stir at 30℃ until the solution is clear. Slowly add this clear solution dropwise to 250.0g of sodium aluminate solution and stir at 30℃ for 1h to obtain a white gel. The molar ratio of the white gel is SiO2:Al2O3:Na2O:H2O = 2.85:1:4.5:190. Transfer this gel to a stainless steel reactor lined with polytetrafluoroethylene and crystallize at 120℃ for 72h. Take out the product, let it cool to room temperature, filter it, and wash the solid product with deionized water until the pH is about 8.0. Dry it at 100℃, and calcine the dried solid at 550℃ for 4h to obtain the comparative X molecular sieve, denoted as D4. Its structural characteristics are shown in Tables 1 and 2.

[0087] The XRD pattern of D4 shows peaks near 2θ = 6.1°, 10.0°, 11.7°, 15.4°, 18.5°, 20.1°, 23.3°, 26.7°, and 30.9°, indicating that D4 is a pure FAU crystalline phase X-zeel. SEM analysis shows that D4 does not exhibit a nanosheet-like stacked crystal morphology; the pore size distribution map shows that D4 has obvious mesoporous distribution peaks; for D4... 27 After fitting and calculating the Al NMR spectrum, it can be seen that... 27 In the Al NMR spectrum, the peak area at the chemical shift of 63 ppm accounts for the total area of ​​the peak. 27 The area of ​​the Al peak is 75.1%; for D4 29 After fitting and calculating the Si NMR spectrum, it can be seen that... 29 The peak area at the chemical shift of -85 ppm in the Si NMR spectrum accounts for the total area of ​​the peak. 29 The area of ​​the Si peak is 30.4%.

[0088] Comparative Example 5 Microporous-mesoporous X molecular sieve D5 was prepared using the same steps as in Example 1, except that: in the first crystallization process of step (3), the temperature was 80℃ and the crystallization time was 72h, and finally the comparative X molecular sieve was obtained, denoted as D5, whose structural characteristics are shown in Tables 1 and 2.

[0089] The XRD pattern of D5 shows peaks near 2θ = 6.1°, 10.0°, 11.7°, 15.4°, 18.5°, 20.1°, 23.3°, 26.7°, and 30.9°, indicating that D5 is a pure FAU crystalline phase X-zeel. SEM analysis shows that D5 does not exhibit a nanosheet-like stacked crystal morphology; the pore size distribution map shows that D5 does not have obvious mesoporous distribution peaks; regarding D5... 27 After fitting and calculating the Al NMR spectrum, it can be seen that... 27 In the Al NMR spectrum, the peak area at the chemical shift of 63 ppm accounts for the total area of ​​the peak. 27 The area of ​​the Al peak is 92.4%; for D5 29 After fitting and calculating the Si NMR spectrum, it can be seen that... 29 The peak area at the chemical shift of -85 ppm in the Si NMR spectrum accounts for the total area of ​​the peak. 29 The area of ​​the Si peak is 35.4%.

[0090] Comparative Example 6 Microporous-mesoporous X molecular sieve D6 was prepared using the same steps as in Example 1, except that: in the second crystallization process of step (4), the temperature was 50°C and the crystallization time was 24h, and finally the comparative X molecular sieve was obtained, denoted as D6, whose structural characteristics are shown in Tables 1 and 2.

[0091] The XRD pattern of D6 shows peaks near 2θ = 6.1°, 10.0°, 11.7°, 15.4°, 18.5°, 20.1°, 23.3°, 26.7°, and 30.9°, indicating that D6 is a pure FAU crystalline phase X-zeel. SEM analysis reveals that D6 exhibits a nanosheet-stacking morphology. The size L of 100 nanosheets was measured in several fields of view. The pore size distribution map shows that D6 has obvious mesoporous peaks. Further analysis of D6... 27 After fitting and calculating the Al NMR spectrum, it can be seen that... 27 In the Al NMR spectrum, the peak area at the chemical shift of 63 ppm accounts for the total area of ​​the peak. 27 The area of ​​the Al peak is 68.2%; for D4 29 After fitting and calculating the Si NMR spectrum, it can be seen that... 29 The peak area at the chemical shift of -85 ppm in the Si NMR spectrum accounts for the total area of ​​the peak. 29 The area of ​​the Si peak is 20.6%.

[0092] Table 1

[0093] Table 2

[0094] As shown in Tables 1 and 2, Examples 1-6, prepared using the method disclosed herein, produced X molecular sieves with a FAU crystalline phase and no EMT. These sieves also possessed suitable micropore and mesopore content and mesopore size, and exhibited nanoparticle stacking forming crystals, which is beneficial for improving the adsorption capacity, adsorption selectivity, and intracrystalline mass transfer ability of the molecular sieve. Comparative Examples 1-6, however, did not employ the method disclosed herein, and the resulting comparative molecular sieves did not possess the beneficial effects of this disclosure. Specifically, while D1 and D4 possessed pure FAU crystalline phases and mesopores, their morphology was that of regular octahedrons with certain surface defects. D2 possessed a mixed FAU and EMT crystalline phase and mesopores. D3 exhibited a small crystal cluster morphology with mesopores. D5 had a regular octahedral morphology with a very low mesopore content. Although D6 possessed a pure FAU crystalline phase and a nanosheet stacked crystal morphology, its framework aluminum and Si(4Al, 0Si) coordinated silicon species content were both low, resulting in low adsorption capacity and adsorption selectivity.

[0095] Test Example 1 The adsorption capacity of the molecular sieve was determined as follows: Nitrogen gas carrying toluene (toluene partial pressure 0.5 MPa) was brought into contact with a certain mass of adsorbent at 35℃ until toluene reached adsorption equilibrium. The adsorption capacity of the tested molecular sieve was calculated based on the mass difference of the molecular sieve before and after toluene adsorption, and the results are listed in Table 3.

[0096] The adsorption selectivity of molecular sieves was determined using a dynamic pulsed experimental setup. This setup consisted of a feed system, adsorption column, heating furnace, and pressure control valve. The adsorption column was a Ф6×1800 mm stainless steel tube, with a molecular sieve loading of 50 mL. The lower inlet of the adsorption column was connected to the feed and nitrogen systems, while the upper outlet was connected to the pressure control valve, which in turn connected to the effluent collector. The desorbent used in the experiment was a mixture of 30 vol% p-diethylbenzene (PDEB) and 70 vol% n-heptane. The pulsed feed solution contained 5.0 vol% ethylbenzene (EB), 5.0 vol% p-xylene (PX), 5.0 vol% m-xylene (MX), 5.0 vol% o-xylene (OX), 5.0 vol% n-nonane (NC9), and 75.0 vol% p-diethylbenzene.

[0097] The method for determining the adsorption selectivity of molecular sieves is as follows: Weigh out molecular sieve particles with a particle size of 300–850 µm, pack them into an adsorption column, and shake to compact. Activate the column under nitrogen atmosphere at 160–190 °C through dehydration. Then, introduce a desorbent to purge the gas from the system. Increase the system pressure to 0.8 MPa and the temperature to 177 °C, stop introducing the desorbent, and allow the column to stand for 1.0 h.-1 An 8 mL pulsed feed solution was introduced at a volume hourly space velocity (VHSV), followed by the desorbent at the same VHSV. Three drops of the desorbate sample were collected every 2 minutes and analyzed by gas chromatography. Desorption curves for each component were plotted with the volume of the desorbent on the x-axis and the concentrations of NC9, EB, PX, MX, and OX on the y-axis. NC9 is not adsorbed and can be used as a tracer to obtain the dead volume of the adsorption system. The midpoint of the tracer's half-peak width (WHM) was taken as the zero point. The net retention volume R from the midpoint of the WHM of each component (EB, PX, MX, and OX) to the zero point was measured. The net retention volume of any component is proportional to the partition coefficient at adsorption equilibrium, reflecting the interaction force between each component and the adsorbent material. The ratio of the net retention volumes of two components is the selectivity β. For example, the ratio of the net retention volume of PX to the net retention volume of EB is the ratio of the adsorption performance of the adsorbent material for PX and EB, i.e., the adsorption selectivity of the adsorbent material for PX relative to EB, denoted as β. P / E Similarly, the adsorption selectivity of the adsorbent material for PX relative to MX and OX is denoted as β. P / M and β P / O The volume of desorbent required for the concentration of MX in the effluent to increase from 10% to 90% at the leading edge of the pulse desorption curve of MX is defined as the adsorption rate [S]. A ] 10-90 The desorbent volume required for the MX concentration to decrease from 90% to 10% after the desorption curve is defined as the desorption rate [S]. D ] 90-10 [S] A ] 10-90 With [S] D ] 90-10 The smaller the value, the higher the mass transfer performance of the adsorption material.

[0098] Table 3

[0099] As shown in Table 3, compared with the comparative X molecular sieves D1~D6, the microporous-mesoporous X molecular sieves A1~A6 prepared in Examples 1~6 of this disclosure can have higher adsorption capacity, p-xylene adsorption selectivity and shorter adsorption / desorption time. When used for the adsorption and separation of C8 aromatic isomers, they can separate p-xylene and have higher adsorption selectivity and mass transfer efficiency.

[0100] The preferred embodiments of this disclosure have been described in detail above with reference to the accompanying drawings. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.

[0101] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.

[0102] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.

Claims

1. A microporous-mesoporous X molecular sieve, characterized in that, The microporous-mesoporous X molecular sieve comprises crystals formed by stacked nanoparticles; The microporous-mesoporous X molecular sieve includes the FAU crystalline phase, and the characteristic peaks of EMT are not present in the XRD pattern. In the microporous-mesoporous X molecular sieve, skeletal aluminum accounts for 90.0% to 99.0% of the total aluminum, and silicon with a chemical environment of Si(4Al, 0Si) accounts for 35.0% to 50.0% of the total silicon. The total pore volume of the X molecular sieve is 0.30~0.45 cm³. 3 / g, the proportion of mesopore volume to total pore volume is 3.0~50.0%, the proportion of micropore volume to total pore volume is 50.0~97.0%, the most probable pore size of mesopores is 2~15nm, and the specific surface area of ​​micropores is 720~760m². 2 / g, mesoporous specific surface area is 20~100m² 2 / g; The average grain size is 0.8~5.0 μm.

2. The microporous-mesoporous X-type molecular sieve according to claim 1, wherein, The nanoparticles include nanosheets, and the size L of the nanosheets in the direction of the minimum size passing through the center is 50~500 nm; Optionally, in the microporous-mesoporous X molecular sieve, the molar ratio of silicon (calculated as SiO2) to aluminum (calculated as Al2O3) is 1.0 to 3.

0.

3. The microporous-mesoporous X-type molecular sieve according to claim 1, wherein, The cations in the microporous-mesoporous X molecular sieve include Na. + and / or K + ; In the microporous-mesoporous X molecular sieve, the total content of Na2O and K2O is 18.0~20.0% by weight.

4. A method for preparing microporous-mesoporous X molecular sieves, characterized in that, The method includes: (1) Mix an inorganic alkali containing metal elements, a silicon source, an aluminum source, and water to obtain a mixture; (2) The mixture is subjected to aging treatment to obtain an aging product; (3) The aging products are subjected to a first-stage crystallization treatment and a second-stage crystallization treatment in sequence; The conditions for the first crystallization treatment include: a temperature of 40~70℃ and a time of 24~96h; The conditions for the second stage of crystallization treatment include: a temperature of 70~150℃ and a time of 6~48h.

5. The method according to claim 4, wherein, The inorganic base containing metal elements includes sodium hydroxide and / or potassium hydroxide; Preferably, the inorganic alkali containing a metal element includes sodium hydroxide and potassium hydroxide, and in the mixture, K + / (K + +Na + The molar ratio of ) is 0.01~1.0, preferably 0.01~0.6; The silicon source includes one or more of water glass, sodium silicate, silica sol, silica fume, ethyl orthosilicate, and methyl orthosilicate; The aluminum source includes one or more of sodium aluminate, low-alkalinity sodium aluminate, boehmite, gibbsite, and aluminum isopropoxide.

6. The method according to claim 4, wherein, In step (1), the molar ratio of silicon (calculated as SiO2) to aluminum (calculated as Al2O3) in the mixture is (2.0~25.0):1, preferably (2.0~15.0):1; the molar ratio of inorganic alkali metal (calculated as metal oxide) to silicon (calculated as SiO2) is (0.6~1.8):1, preferably (1.0~1.5):1; and the molar ratio of H2O to aluminum (calculated as Al2O3) is (120.0~220.0):1, preferably (140.0~190.0):

1.

7. The method according to claim 4, wherein, In step (1), the mixing is carried out under stirring conditions, including a temperature of 10~50℃ and a time of 0.5~3h.

8. The method according to claim 4, wherein, In step (2), the aging treatment conditions include: a temperature of 5~35℃ and a time of 6~36h.

9. The method according to claim 4, wherein, In step (3), the conditions for the first crystallization treatment include: a temperature of 50~60℃ and a time of 72~84h.

10. The method according to claim 4, wherein, In step (3), the conditions for the second crystallization process include: a temperature of 80~110℃ and a time of 12~24h.

11. Microporous-mesoporous X molecular sieve prepared by the method according to any one of claims 4 to 10.

12. A method for adsorption separation of p-xylene from C8 mixed aromatics, the method comprising: A C8 mixed aromatic hydrocarbon containing p-xylene is contacted with an adsorbent for adsorption to obtain a molecular sieve with adsorbed p-xylene; characterized in that the adsorbent comprises the microporous-mesoporous X molecular sieve according to any one of claims 1 to 3 and 11.

13. The method according to claim 12, wherein, The adsorption conditions include: a pressure of 0.3~1.5MPa and a temperature of 120~190℃.

14. The method according to claim 12, wherein, The method further includes: contacting the molecular sieve that adsorbed p-xylene with a desorbent to desorb it; The desorbent includes p-ethylbenzene and / or toluene; The desorption conditions include: a pressure of 0.3~1.5MPa and a temperature of 120~190℃.

15. The method according to claim 12, wherein, The C8 mixed aromatics include ethylbenzene, p-xylene, m-xylene, and o-xylene.

Citation Information

Patent Citations

  • Zeolite adsorbents prepared from X zeolite with low binder content and low external surface area, their preparation methods and applications.

    CN107107026B

  • A mesoporous X zeolite and its adsorbent and preparation method

    CN109692657B

  • Aromatic hydrocarbon separation by adsorption

    US3558730A

  • Zeolitic adsorbent for xylene separation

    US3960774A